2014
DOI: 10.1111/caim.12089
|View full text |Cite
|
Sign up to set email alerts
|

Emotions as Constraining and Facilitating Factors for Creativity: Companionate Love and Anger

Abstract: Generally the literature has favoured the notion that positive affect facilitates creative performance. However, a recent critical review has demonstrated that negative affect can enhance cognitive performance and improve motivation. Moreover, with a few exceptions, previous research comparing positive and negative affect as either a facilitator of or a constraint on creativity factors has rested primarily on the valence approach. Unfortunately, the results were mixed. This paper explores the effects of two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 70 publications
2
33
0
1
Order By: Relevance
“…Based on the results obtained from this study, evidence shows that passion for inventing is significantly linked to creativity, coinciding with previous results (Cardon et al, 2013;Luh & Lu, 2012). However, these results cannot be considered definite, since previous research has found that negative affect also influences creativity (Bledow et al, 2013;Yang & Hung, 2015). Empirical evidence from different sources supports the assumption that negative affect can contribute to creativity.…”
Section: Key Findings and Contributionssupporting
confidence: 89%
See 1 more Smart Citation
“…Based on the results obtained from this study, evidence shows that passion for inventing is significantly linked to creativity, coinciding with previous results (Cardon et al, 2013;Luh & Lu, 2012). However, these results cannot be considered definite, since previous research has found that negative affect also influences creativity (Bledow et al, 2013;Yang & Hung, 2015). Empirical evidence from different sources supports the assumption that negative affect can contribute to creativity.…”
Section: Key Findings and Contributionssupporting
confidence: 89%
“…Along the same lines, Hayton and Cholakova (2012) mention that affect not only influences creativity through the generation of business ideas, it also influences the intent to improve them. However, evidence contradicting these results has also been found, and negative affect also stimulates creativity under certain circumstances (Bledow, Rosing & Frese, 2013;George & Zhou, 2002, 2007Kaufmann, 2015;Kaufmann & Vosburg, 2002;Yang & Hung, 2015). Therefore, it is still impossible to generalize the relationship between positive affect and creativity.…”
Section: Entrepreneurial Passion and Creativitymentioning
confidence: 99%
“…It should be pointed out that in our sample, EFCR had no effect on creative corporate culture (Model 1), a finding supported by the literature, according to which crises and financial restrictions at the organizational level have a positive impact on creativity as firms resort to innovation in the hope of turning business around (Yang and Hung, 2015).…”
Section: Analysis and Discussionsupporting
confidence: 82%
“…The participants and control groups in this study are MBA students. Recent research on creative team process has shown that empirical results from student samples can inform the work of innovation managers in the design thinking and creativity domain (Amabile et al, 2005;Bissola et al, 2014;Seidel and Fixson, 2013;Yang and Hung, 2015). With respect to generalisability of findings from a student sample, Chiocchio and Essiembre (2009, p.386) note that "teams of undergraduate and graduate students are as real as any other type of teams".…”
Section: Participants and Control Groupsmentioning
confidence: 99%